Governing the dead Sovereignty and the politics of dead bodies - Stepputat, Finn (Manchester University Press, 2020)
This book looks at sovereignty as a particular form of power and politics. It shows that the fate of bodies in the transition from life to death can provide a key to understanding fundamental ways in which sovereignty is claimed and performed. The contributions analyse (post-)conflict as well as non-conflict contexts, which too often are studied in isolation from one another. Focusing on contemporary issues rather than the equally important historical dimensions, they all grapple with the questions of who governs the dead bodies, how, why and with what effects. The book analyses how dead bodies are placed and dealt with in spaces between competing, overlapping and nested sovereign orders, under normal as well as exceptional conditions. It looks at contributions that draw on psychoanalysis, critical theory, the structuralist-functionalist anthropology of burial rituals and recent ideas of agency and materiality. The book first explains the efforts of states to contain and separate out dead bodies in particular sites. It explores the ways in which such efforts of containment are negotiated and contested in struggles between different entities that claim the dead bodies. The book then shows how entities that claim sovereignty produce effects of sovereignty by challenging and transgressing the laws regarding the legitimate use of violence and how dead bodies should be treated with dignity.